2018
DOI: 10.1007/s11064-018-2508-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes and Expression of PCNA and RPE65 in Sodium Iodate-Induced Acute Retinal Pigment Epithelium Degeneration Model

Abstract: Alteration in retinal pigment epithelium (RPE) results in the visual dysfunction and blindness of retinal degenerative diseases. Injection of sodium iodate (NaIO) generates degeneration of RPE. We analyzed the sequential ultrastructure and expression of proliferating cell nuclear antigen (PCNA) and retina-specific RPE65 in NaIO-induced retinal degeneration model. Adult male rats were injected 1% NaIO (50 mg/kg) and eyes were enucleated at 1, 3, 5, 7 and 14 days post-injection (DPI), fixed, and processed for hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
3
6
0
Order By: Relevance
“…RPE65-positive cells were rarely observed even at ONL, PR layer ( Figure 4B , arrow heads), and the inward moving RPE65-possitive cells were not stained by phalloidin. The morphology of intra-retinal migrating RPE cells was also not epithelium, suggesting an epithelial to mesenchymal transition of RPE cells, similar to a report from another SI-induced retina damage ( 13 ). Further, activated RPE migration has been reported in human AMD as an early AMD phenotype ( 16 , 17 ) and in rat SI-damaged retina ( 13 ).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…RPE65-positive cells were rarely observed even at ONL, PR layer ( Figure 4B , arrow heads), and the inward moving RPE65-possitive cells were not stained by phalloidin. The morphology of intra-retinal migrating RPE cells was also not epithelium, suggesting an epithelial to mesenchymal transition of RPE cells, similar to a report from another SI-induced retina damage ( 13 ). Further, activated RPE migration has been reported in human AMD as an early AMD phenotype ( 16 , 17 ) and in rat SI-damaged retina ( 13 ).…”
Section: Resultssupporting
confidence: 88%
“…The morphology of intra-retinal migrating RPE cells was also not epithelium, suggesting an epithelial to mesenchymal transition of RPE cells, similar to a report from another SI-induced retina damage ( 13 ). Further, activated RPE migration has been reported in human AMD as an early AMD phenotype ( 16 , 17 ) and in rat SI-damaged retina ( 13 ).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…We and others have shown that the RPE damage results from increased ROS levels both in vitro and in vivo [10,31,32,33]. Several oxidative stress regulatory pathways such as Akt phosphorylation, PTEN, Nrf2, and mTOR have been shown to be involved [32,34,35]. The mechanism of cell death in RPE with NaIO3 is through apoptotic pathways although necroptosis has also been reported [36].…”
Section: Discussionmentioning
confidence: 99%